Switch Catalysis To Deliver Multi‐Block Polyesters from Mixtures of Propene Oxide, Lactide, and Phthalic Anhydride. Issue 51 (26th November 2018) - Stößer, Tim; Mulryan, Daniel; Williams, Charlotte K.
Abstract: Switchable polymerisation catalysis enables block polymer sequence selectivity from monomer mixtures, resulting in the formation of multiblock polyesters. The aluminium salphen catalyst switches between two different polymerisation mechanisms and selectively enchains mixtures of commercially available monomers: lactide, phthalic anhydride, and propene oxide. Sequential monomer mixture additions yield multi‐block polyesters featuring 3, 7, 11, 15, 19, 23, and 27 blocks. The unparalleled catalytic selectivity can be used to access completely new multi‐block polyesters relevant for future applications. Abstract : Mixtures of three commercial monomers, produced and used at large scale in existing polymer manufacturing, were applied in a switchable catalytic process to deliver new multi‐block polyesters. The aluminium catalyst delivers polymers of 3, 7, 11, 15, 19, 23, and 27 block units with outstanding selectivity.